Level of Adequacy of Nutrition, Physical Activity and Nutritional Status Youth Soccer Athlete - Arimbi, Arimbi; Wahid, Wahyana Mujari; Arfanda, Poppy Elisano; Usman, Arifuddin; Muriyati, Muriyati (Department of Physical Education, Sport, Health and Recreation, 2023)
The research purpose to determine the level of nutritional adequacy, physical activity and nutritional status of adolescent soccer athletes. The research was conducted on teenage soccer athletes who are members of the PERSIS Makassar soccer club, which totals 27 teenage athletes. The research method used is a case study presented descriptively. Nutritional intake was measured using the food recall method for 3 x 24 hours using a food composition list (DKBM). Physical activity is categorized into three levels, namely heavy, moderate and light using WHO calculations. Nutritional status is calculated based on body mass index for age (BMI/U). The nutritional adequacy level of the sample was classified into two categories, namely adequate if the nutritional adequacy level was >80% and categorized as insufficient if the nutritional adequacy level was <80%. The results of a 24 hour food recall for 3 days obtained an average sample energy intake level of 14 (51.85%) people who had good energy intake and 13 (48.15%) people with less energy intake and no athletes (0%) ) who have more energy intake. The results of the questionnaire summary were obtained which were matched with WHO physical activity category standards, it was seen that all soccer athletes (100%) had heavy physical activity categories while the nutritional status of the anthropometric data obtained, it was obtained that there were 14 athletes with normal nutritional status (51, 85%), 13 people (48.15%) were underweight, and 0% were athletes in the category of fat and very thin.